LINGUISTIC STATUS OF LANGUAGE INTERNET COMMUNICATIONS (Journal of Universal Science Research, 2023)
In this article we study the linguistic status of Internet Communications formed in the present conditions of the information society, and such slang can be nominated as a national version of the meta-language that possesses a novel function of the language. This function overwhelms non-verbal participants of communication interactions regardless of their nationality and command of any language.